Production of Xylooligosaccharides from oil palm fronds hemicellulose by trichoderma longibra chia tum xylanase and ultrafiltration / Siti Normah Mohd Damanhuri Shah - Mohamad Damanhuri Shah, Siti Normah (2015)
Oil palm fronds (OPF) are cheap, widespread and largely available throughout the year. OPF contains rich hemicellulose which can be hydrolysed by enzyme for production of xylooligosaccharides (XOs). The aim of this study was to produce high yield of XOs from OPF hemicellulose. XOs production was performed by enzymatic hydrolysis of hemicellulose which was obtained by alkaline extraction from the OPF. OPF hemicellulose was hydrolysed using an endo-xylanse from Trichoderma longibrachiatum and the effects of different pH, temperature, enzyme and substrate concentration and hydrolysis time on the XOs yield were investigated. The hydrolysate containing XOs was then fractionated by ultrafiltration using 10 kDa, 3 kDa and 1 kDa molecular weight cut off (MWCO) membrane to purify the crude of XOs. The maximum yield of XOs (46%) was obtained at pH 4.6, temperature of 4°C, enzyme concentration of 2 U/ml and substrate concentration of 2% for 8 hours hydrolysis time with a considerable amount of xylose (12.55%). The percent recoveries of XOs in the final permeate of 3 kDa and 1 kDa MWCO membrane were 78.32% and 76.18%, respectively. The results showed that 3 kDa MWCO membrane fractionated XOs better than 1 kDa MWCO membrane with low amount of monosaccharides and high yield of xylobiose (X2) and xylotriose (X3). The results indicated the potential utilization of OPF for the production of XOs by enzymatic hydrolysis, which could be further extended as functional food ingredients.